United States : 2002 Article IV Consultation-Staff Report; Staff Supplement; and Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This 2002 Article IV Consultation highlights that the United States economy slipped into recession in early 2001, as industrial production dropped sharply, investment and exports declined, and employment and weekly hours fell. The downturn was triggered in part by the collapse of the Information Technology boom and stock prices in March 2000, but was further exacerbated by the September 11th terrorist attacks. As a result, following real GDP growth in excess of 4 percent during the previous four years, the economy slowed sharply in 2001.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet